User experience comparative analysis between a digital edition and a hard copy of a magazine (Human Factors in Design, 2023)
This research aims to demonstrate the results of the user experience ergonomic analysis between a printed magazine and its digital equivalent. The editorial title chosen was Editora Globo's Casa e Jardim magazine. 24 tests were carried out with 12 participants, which were divided into two age groups and two groups of familiarity with the use of the iPad. The participants participated in an ergonomic test to perform 6 tasks each (3 on digital and 3 on printed support). During the test, the time required to perform each proposed task was measured. In addition, the participants answered a satisfaction questionnaire focused on the user experience (adaptation of the SUS protocol) and were subsequently interviewed about the answers given in this form to obtain descriptive data about the quantitative results. Practically in all subgroups and in all 3 tasks, the average time for completion was shorter when using the printed magazine. The only exception was with the group of 25-39 years old experienced in using the iPad to perform task 1. When observing the score obtained by each sample group and the entire sample in the questionnaire, it is possible to state that there is a difference perception of satisfaction between the two supports and that the printed magazine has a better user experience (p = 0.003 ≤ α = 0.05). In all 10 specific questions asked about each support and answered on a likert scale of the questionnaire, the printed magazine obtained a better result compared to the application.
Keywords: ergonomics; user experience; satisfaction; editorial object